Chronological Sequence of Leaf Phenology, Xylem and Phloem Formation and Sap Flow of Quercus pubescens from Abandoned Karst Grasslands - Lavrič, Martina; Eler, Klemen; Ferlan, Mitja; Vodnik, Dominik; Gričar, Jožica (Frontiers in Plant Science, 2017)
Intra-annual variations in leaf development, radial growth, including the phloem part, and sap flow have rarely been studied in deciduous trees from drought-prone environments. In order to understand better the chronological order and temporal course of these processes, we monitored leaf phenology, xylem and phloem formation and sap flow in Quercus pubescens from abandoned karst grasslands in Slovenia during the growing season of 2014. We found that the initial earlywood vessel formation started before bud opening at the beginning of April. Buds started to open in the second half of April and full leaf unfolding occurred by the end of May. LAI values increased correspondingly with leaf development. About 28 % of xylem and 22 % of phloem annual increment were formed by the time of bud break. Initial earlywood vessels were fully lignified and ready for water transport, indicating that they are essential to provide hydraulic conductivity for axial water flow during leaf development. Sap flow became active and increasing contemporarily with leaf development and LAI values. Similar early spring patterns of xylem sap flow and LAI denoted that water transport in oaks broadly followed canopy leaf area development. In the initial three weeks of radial growth, phloem growth preceded that of xylem, indicating its priority over xylem at the beginning of the growing season. This may be related to the fact that after bud break, the developing foliage is a very large sink for carbohydrates but, at the same time, represents a small transpirational area. Whether the interdependence of the chronological sequence of the studied processes is fixed in Q. pubescens needs to be confirmed with more data and several years of analyses, although the ‘correct sequence’ of processes is essential for synchronized plant performance and response to environmental stress.